2021
DOI: 10.1007/s00726-021-02982-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acidic pH on the adsorption and lytic activity of the peptides Polybia-MP1 and its histidine-containing analog in anionic lipid membrane: a biophysical study by molecular dynamics and spectroscopy

Abstract: Antimicrobial peptides (AMPs) are part of the innate immune system of many species and are compounds with potential application against the development of resistant bacterial strains promoted by conventional antibiotics. The AMPs are rich in cationic and hydrophobic residues and act directly on the lipidic phase of the cell membranes. The MP1 has a broad-spectrum bactericide activity in both Gram-negative and positive bacteria, not being hemolytic or cytotoxic. H-MP1 is a synthetic analog of MP1 with lysines r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 75 publications
2
19
0
Order By: Relevance
“…Ingeniously masking positive charges of ACPs is a promising strategy to enhance selectivity and reduce toxicity . Some acid-activated anticancer peptides or recombinant peptides have been developed using the protonation of histidine in an acidic environment, like substituting lysines/arginines for histidines or fusing with specific binding peptides. ,, Previously, we have also obtained a series of pH-responsive anticancer peptides by histidine substitutions and introduction of anionic binding peptides based on the short cationic α-helical ACP LK. , In addition, we found that the coupling of anionic binding peptides to cationic LK could play a major role in improving peptide stability. Thus, the anionic peptide fusion strategy might be a good approach to obtain the pH selectivity concomitant with enhancing the stability of ACPs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ingeniously masking positive charges of ACPs is a promising strategy to enhance selectivity and reduce toxicity . Some acid-activated anticancer peptides or recombinant peptides have been developed using the protonation of histidine in an acidic environment, like substituting lysines/arginines for histidines or fusing with specific binding peptides. ,, Previously, we have also obtained a series of pH-responsive anticancer peptides by histidine substitutions and introduction of anionic binding peptides based on the short cationic α-helical ACP LK. , In addition, we found that the coupling of anionic binding peptides to cationic LK could play a major role in improving peptide stability. Thus, the anionic peptide fusion strategy might be a good approach to obtain the pH selectivity concomitant with enhancing the stability of ACPs.…”
Section: Discussionmentioning
confidence: 98%
“…31 Some acid-activated anticancer peptides or recombinant peptides have been developed using the protonation of histidine in an acidic environment, like substituting lysines/ arginines for histidines or fusing with specific binding peptides. [32][33][34]38,39 Previously, we have also obtained a series of pH-responsive anticancer peptides by histidine substitutions and introduction of anionic binding peptides based on the short cationic α-helical ACP LK. 36,37 In addition, we found that the coupling of anionic binding peptides to cationic LK could play a major role in improving peptide stability.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Experimental findings have shown that, in an acidic environment, MP1 presents an affinity to the membrane 1.5 times higher than H-MP1. 11 In addition, H-MP1 has a shallower insertion and about three times less lytic activity than MP1. 11 Details on how charge distribution, size of charged side chains, and secondary structure of AMPs affect the binding to the membrane remain unclear, 56−58 although the α-helix structure of AMPs might be important to decrease toxicity.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Its adsorption to the bacterial membrane is followed by their α-helix structuring, modulated by electrostatic and hydrophobic interactions. After adsorption, according to the orientation of the peptides, changes in several physical properties of the membrane can be observed, such as thickness, decrease in the order parameter of the acyl chains, and alterations of membrane phase behavior. , …”
Section: Introductionmentioning
confidence: 99%
“…Several AMP families have been reported to possess various secondary structures. For example, cecropins [47], lasioglossins [48], melittin [49] and Polybia-MP1 [50][51][52] form α-helical regions. Insect defensins form β-sheet conformations or proline/glycine-rich peptides [53], for example, drosocin [54], lebocins and attacin [55] show extended structures.…”
Section: Insectsmentioning
confidence: 99%